(i) 1/a + b + x = 1/a + 1/b + 1/x
⇒ 1/a + b + x – 1/x = 1/a + 1/b
⇒ x – a – b – x/x(a + b + x) = 1/a + 1/b
-(a + b)/x(a + b + x) = a + b/ab
⇒ x(a + b + x)(a + b) = -(a + b)ab
⇒ x(a + b + x)(a + b) + ab(a + b) = 0
⇒ (a + b){x(a + b + x) + ab} = 0
⇒ a + b or x(a + b + x) + ab = 0
But a + b ≠ 0
So x(a + b + x) + ab = 0
⇒ x(a + b) + x^{2} + ab = 0
⇒ x^{2} + ax + bx + ab = 0
⇒ x(x + a) + b(x + a) = 0
⇒ (x + a)(x + b) = 0
⇒ x = - a or x = - b
(ii) 4x^{2} – 4ax + (a^{2} – b^{2}) = 0
Where a, b ∈ R
⇒ 4x^{2} – {2(a + b)x + 2(a – b)x} + a^{2} – b^{2} = 0
⇒ {4x^{2} – 2(a + b)x} - {2(a – b)x – (a^{2} – b^{2})} = 0
⇒ 2x{2x – (a + b)} – (a – b) {2x – (a + b)} = 0
⇒ {2x – (a + b)} {2x - (a – b)} = 0
⇒ 2x – (a + b) = 0
or 2x – (a – b) = 0
⇒ x = a + b/2 or x = a – b/2